DIVERSITY OF ODONATA IN LANGSA URBAN FOREST, LANGSA, ACEH, INDONESIA - Sayed Latiful Asrori; Kartika Aprilia Putri; Siti Diniarsih; Pungki Lupiyaningdyah; Herlina Putri Endah Sari (BRIN Publishing (Penerbit BRIN), 2023)
Odonata is important as environmental bioindicator as well as pest control. Langsa Urban Forest (LUF) is a 10-ha green open space in Langsa City, Aceh Province which serves the purpose of tourism and support biodiversity conservation, in which Odonata (dragonflies and damselflies) is included. Thereis a lack of Odonata research in Langsa, especially at the LUF area, therefore this study offers a baseline information for wildlife management. Field observations had been conducted between February to March 2022 using line-transect method. As a result, this study recorded 19 Odonata species from four families, of which Orthetrum sabina (Libellulidae) became the most prominent species observed. Odonata diversity in LUF was medium (H’ = 1.863-2.252) with population of each species presumed to be nearly even (J = 0.71-0.79). Odonata diversity in LUF serves as additional information on Odonata species found in Indonesia, especially Aceh Province. Also, the medium category of Odonata diversity index in LUF can be used as a reference for LUF management to support more ecosystems as Odonata habitat.